L’impronta della memoria: per un’archeologia degli usi politici del passato - Lorenzo Migliorati (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
Memory and trauma are closely interrelated notions, fully modern and no inert. The paper reconstructs the parabola of these concepts, starting from their appearance in scientific debate to observe their evolution and use in public and political debate. Both born under the sign of suspicion, the ideas of collective memory and of trauma have been fully integrated into the public space, granting them citizenship rights and originating new veridical political subjectivities: the witness and the traumatized. Advanced modernity, the accelerating processes of the contemporary, the multiplication of testimonial sources, and, not least, a certain current social and political destabilization--of which the pandemic is only the latest (indeed, already the penultimate, perhaps the third-last) example--have produced a new rémise en question of the forms of representation of pain and memory in the contemporary. The politics of evidence rises to the source of truthfulness. Even in the face of the most unspeakable pain.